In Silico Assessment of Naphthalene Interaction with Glutathione Reductase and Histological Changes in Naphthalene Exposed Rats Tissues - Agboola, Olubukola; Olaoye, Ige; Awotula, Ayodeji; Oso, Babatunde; Akhigbe, Godswill; Nwaoha, Peace (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Naphthalene (NA), a bicyclic aromatic compound that is widely used in various commercial and industrial applications including lavatory scent disks and mothballs, is known to be readily absorbed into the systemic circulation following either inhalation or ingestion and may cause systemic toxicity. This study examined the histopathological changes in some tissues (lung, liver and kidney) of NA-exposed Wistar rats. Twenty-four rats (175-250 g) were randomly divided into six groups of four rats each. The rats in all groups were given food and water while in addition rats in the experimental groups were exposed to NA at 0.75 mg/m3 and 1.50 mg/m3 for 2 h and 4 h. Rats were sacrificed at 24 h after the last hour of NA exposure. The tissues were excised for histological examination. The effects of NA and some selected metabolites using the rat glutathione reductase homology model were examined via molecular docking and dynamic simulation. From this study, exposure of rats to NA resulted in hepatocyte necrosis at 0.75 mg/m3 for 2 h, dilation of the alveolar duct of the lung at 0.75 mg/m3 and severe epithelial hyperplasia and chronic infiltration of inflammatory cells in the lung at 1.50 mg/m3 for 4 h. Also, vascular congestion was observed in the kidneys at 0.75 mg/m3 for 2 h and 1.50 mg/m3 for 4 h. The in silico study revealed the NA metabolite toxic potential, and NA showed the lowest binding score (-5.40± 0.00 kcal/mol). Therefore, the study concludes that NA exposure irrespective of duration can lead to hepatic and alveolar damage in the absence of mechanisms that can ameliorate its toxic effects.